The Vital Lung Capacity of Employees with Risk Factors for Potential Exposure to Ammonia Gas - Ibrahim Edy Sapada; Wita Asmalinda (Poltekkes Kemenkes Jakarta III, 2020)
The fertilizer industry produces several pollutants such as ammonia gas, urea dust, smoke, particulates. Workers are exposed to air inhalation at work, entering the respiratory system, which is the main toxic entry point. The risk of workers being exposed to lung disease due to inhalation of dust/ smoke/ harmful gases in the work environment. It will increase if workers do not comply with protecting themselves from risk factors and potential accompanying factors such as smoking habits excessive body mass index. Lung ventilation is the entry and exit of air between the atmosphere and the pulmonary alveoli. This study aimed to determine the correlation between body mass index, smoking habits, and hemoglobin levels with vital lung capacity to P.T. Pupuk Sriwidjaja Palembang employees. The design of this study is a cross-section. The research was conducted at P.T. Pupuk Sriwidjaja for 30 days. The research sample was 78 employees of the ammonia unit. Data analysis found a significant correlation between vital lung capacity with body mass index (p-value = 0.009), and hemoglobin levels (p-value = 0.039). There was no significant correlation between smoking habits and vital lung capacity values (p-value = 0.449). It can be concluded that body mass index, smoking habits, and hemoglobin levels correlate with vital lung capacity.